SYARIAH COMPLIANT HOTEL: THE CONCEPT AND PRACTICES - Suroso -; Welly Ardiansyah; M. Ridhwan (Politeknik Negeri Sriwijaya, 2016)
The demand for and supply of Islamic hospitality services has been affected positively by the increasing number of Islamic followers globally and positive tourism trends. This study is discussing on Syariah Compliant hotel concept and practices, the outline of operations, design and finance system. Therefore the hotel management must try to address the need to enhance the development of Islamic Tourism through the improvement of its current tourism infrastructure, focusing on the establishment of Syariah-Compliant Hotel using a conceptual framework developed specifically to expose the factors required for any Muslim country to be successful in today’s highly competitive hospitality market.